Doppler studies in normal kidneys of preterm and term neonates - Changes in relation to gestational age and birth weight - Yildrim, H; Gungor, S; Cihangiroglu, MM; Aygun, AD (Wiley, 2005)
Objective. The purpose of this study was to establish normative data for the flow velocity waveform indices of the renal arteries in the neonatal population and to evaluate the differentiation between birth weight and gestational age of neonates. Methods. Color sonography was performed in 65 neonates on the fifth day of life. Mean flow velocity was assessed, and measurements of the systolic/diastolic velocity ratio, resistive index, and pulsatility index were performed by online calculation. Results. All established values of renal arteries showed no significant differences in the right and left kidneys (P > .05). These values were not correlated with gestational age and birth weight (P > .05). Conclusions. Peak systolic velocity, systolic/diastolic velocity ratio, and resistive index and pulsatility index values remain stable despite gestational age or birth weight and not different between the right and left kidneys.
Keywords: mean flow velocity; preterm neonate; pulsatility index; resistive index; term neonate